A novel bioelectrochemical strategy for efficient treatment of saline-alkaline and oligotrophic sulfate wastewater mediated by bacterial electron shuttling. (February 2023) - Shen, Hongyan; Zhang, Zhitao; Chen, Zheng; Shen, Jiachang; Wen, Qifeng; Jia, Yunpu; Yu, Chenxi; Wei, Gaojie; Mu, Tingzhen; Miao, Delu; Yang, Maohua; Xing, Jianmin
Abstract: Sulfate-rich wastewater from industrial processes with the characteristics of high salinity, high pH and oligonutrition is difficult to be treated by traditional anaerobic process. In this study, a microbial electrolysis cell (MEC) coupled with electroactive haloalkaliphilic sulfate reducing bacteria was applied to sulfate removal for the first time in an extreme environment (0.83 M Na + and pH 9.7). In the anode, bacteria as electron shuttles and sulfide-driven continuous electron donors as exogenous electrons provided to cathodic sulfate removal. After several months of electrical acclimation and adaptation, the electroactive microorganisms in the bipolar showed more electrical activity than expected. When the potential was controlled at 0.3 V (vs Ag/AgCl), the maximum current density reached 3753 mA/m 2, and the maximum sulfate removal rate and electron utilization efficiency reached to 85.9 % and 88 %, respectively, which were higher than the traditional bioelectrochemical methods. The results of 16S rRNA gene sequence alignment showed that the Desulfurivibrio AMeS2 was dominant on the anode electrode, and a large number of similar conductive flagella were observed, which indicated that it was likely to have the function of transferring electrons to the outside of the cell. The dominance of the genus, Desulfonatronovibrio, in the biofilm on the cathode electrode implied that it might realize the reduction of sulfate by accepting external electrons under malnutrition condition, and might be a candidate bacterium for sulfate removal in extreme industrial wastewater. This bioelectrochemical technology combined with extremophile electroactive microorganisms provides a new strategy to make up for the deficiencies of traditional treatments. Graphical abstract: Unlabelled Image